Digital Based Literacy Learning Integration to Increase The Appreciation and Creativity of High School Students - Farniati, Farniati; Arwan, Arwan; Haris, A. (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to examine the effectiveness of digital-based literary learning in enhancing high school students’ literary appreciation and creativity. The background of the study lies in the low student interest in literary learning, which is often delivered using conventional methods with limited media integration. This research employed a mixed-methods approach with an embedded design, combining quantitative data from pretests and posttests with qualitative data from observations and interviews. The intervention was conducted over four sessions using digital platforms such as Canva and Padlet to support both literary appreciation and creative production. The paired sample t-test results showed a significant improvement between pretest and posttest scores, indicating the effectiveness of the digital approach. Moreover, qualitative findings revealed that students were more enthusiastic, expressive, and engaged throughout the learning process. In conclusion, digital literary learning is an innovative instructional approach that responds to the challenges of modern literacy and is highly recommended for broader implementation in secondary education.